Infection as an important factor in medication-related osteonecrosis of the jaw (MRONJ) - Otto, Sven; Aljohani, Suad; Fliefel, Riham; Ecke, Sara; Ristow, Oliver; Burian, Egon; Troeltzsch, Matthias; Pautke, Christoph; Ehrenfeld, Michael (Medicina, 2021)
Medication-related osteonecrosis of the jaw (MRONJ) has become a well-known side effect of antiresorptive, and antiangiogenic drugs commonly used in cancer management. Despite a considerable amount of literature addressing MRONJ, it is still widely accepted that the underlying pathomechanism of MRONJ is unclear. However, several clinical and preclinical studies indicate that infection seems to have a major role in the pathogenesis of MRONJ. Although there is no conclusive evidence for the infection hypothesis yet, available data have shown a robust association between local infection and MRONJ development. This observation is very critical in order to implement policies to reduce the risk of MRONJ in patients under antiresorptive drugs. This critical review was conducted to collect the most reliable evidence regarding the link between local infection and MRONJ pathogenesis.